Assessing Perception of Climate Change by Representatives of Public Authorities and Designing Coastal Climate Services: Lessons Learnt From French Polynesia - Terorotua, Heitea; Duvat, Virginie K. E.; Maspataud, Aurélie; Ouriqua, Jehane (Frontiers in Marine Science, 2020)
Institutional actors have a crucial role in adaptation to climate change, especially for highly vulnerable territories such as small tropical islands. Here, we emphasize their major role in the co-design of tailored coastal climate services based on a case study of French Polynesia. In this perspective, we assessed climate change perceptions by public authorities and identified their needs with regard to climate-related science. This assessment included an analysis of the decision-making context, semi-structured interviews with practitioners representing 23 administrative divisions directly or indirectly involved in climate change issues, and a workshop dedicated to discussing needs in terms of coastal climate services. Generally, respondents did not identify climate change as a major current issue in French Polynesia; they showed more concern for economic growth, pollution, land tenure, and land use planning. However, interviewees were concerned about future impacts of sea-level rise (SLR) and ocean warming and acidification, mentioning in particular their detrimental impacts on marine ecosystems, shoreline position, economy (especially agriculture and the blue economy), and freshwater resources. The interviewed practitioners showed particular interest in SLR projections for future decades up to a century, and for knowledge on expected impacts to critical infrastructure, coastal systems, and natural resources. Practitioners’ needs made it possible to co-define four coastal climate services to be developed: (1) the design of sea-level-rise-compatible critical infrastructures (airports and ports); (2) adapting to the risk of destabilization of beaches and reef islands; (3) professional training on climate change impacts and adaptation, including an analysis of potentially emerging new jobs in the SLR context; and (4) the development of participatory approaches for observing climate change impacts. While the co-development of these coastal climate services will require a multi-year engagement of stakeholders concerned with climate change adaptation, our results already shed light on specific needs for salient coastal climate services in highly vulnerable tropical island territories.